2019
DOI: 10.22158/selt.v7n1p59
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender, Experience, and Training on Teachers’ Written Corrective Feedback Practices

Abstract: <p><em>This study investigated whether EFL Post-Basic education teachers’ perceptions toward teachers’ practice of written corrective feedback (WCF) varied according to three contextual variables gender, teaching experience, and in-service training on WCF. It also attempted to investigate the challenges teachers encounter when providing WCF. The quantitative data was collected from 156 EFL teachers who were teaching Post-Basic education grades (11-12). The participants were randomly selected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…For example, some participants said that complete indirect feedback, especially in the form of codes, confused them and consequently neglected the comments. This is in line with Saadat et al (2017) and Al Kharusi et al (2019), who found that if students think that feedback is not informative, they tend to ignore it. This demonstrates that the strategy adopted by instructors in providing WCF could be one of the most significant determinants of how students respond.…”
Section: The Impact Of Saudi Culture On Students' Reactions To Writte...supporting
confidence: 85%
“…For example, some participants said that complete indirect feedback, especially in the form of codes, confused them and consequently neglected the comments. This is in line with Saadat et al (2017) and Al Kharusi et al (2019), who found that if students think that feedback is not informative, they tend to ignore it. This demonstrates that the strategy adopted by instructors in providing WCF could be one of the most significant determinants of how students respond.…”
Section: The Impact Of Saudi Culture On Students' Reactions To Writte...supporting
confidence: 85%